P416 A NOT–SO–RARE COMPLICATION OF CONNECTIVE TISSUE DISEASE. (18th May 2022) - Bonadies, D; Palumbo, R; La Manna, M; Santopietro, M; Sorvillo, G; Visco, V; Vigorito, F; Ciccarelli, M; Galasso, G; Vecchione, C; Soriente, L
Abstract: Pulmonary hypertension is a not–so–rare complication of connective tissue diseases and is usually related with an inauspicious prognosis.We present the case of a 67–years–old woman hospitalized for progressive dyspnea. Two–dimensional echocardiography showed numerous features related to pulmonary hypertension (PH) with moderate Mitral Regurgitation. The right cardiac catheterization confirmed mixed PH (pre and post capillary) without chest angio–TC evidence of pulmonary thromboembolism. Thanks to optimized medical therapy (B–Blocker, ACE–i and diuretics), there was a significant clinical improvement documented at discharge. After 1 year, due to recurrence of dyspnea, she was admitted to our medical unit. Her clinical examination showed some of the characteristics of a connective tissue disease. Compared to previous echocardiography, a moderate to mild reduction of MR was documented. Chest CT scan revealed interstitial lung disease likely related to patient's underlying pathology. Immunological screening tests detected the presence of antinuclear (ANA) and anti–topoisomerase (ATA) antibodies. Right heart catheterization documented a worsening of PH with only pre–capillary component. On the basis of the above findings, a diagnosis of CREST syndrome complicated with PH was made, and the patient was started on oral combination of macitentan and riociguat. The frequency of this complication in connective tissue disease, the need for screening tests and different treatment approaches of pre and post capillary pulmonary hypertension is discussed.